Clinical practice guidelines from the French National Society of Coloproctology in treating chronic constipation. Issue 4 (April 2018) - Vitton, Veronique; Damon, Henri; Benezech, Alban; Bouchard, Dominique; Brardjanian, Sarah; Brochard, Charlène; Coffin, Benoit; Fathallah, Nadia; Higuero, Thierry; Jouët, Pauline; Leroi, Anne-Marie; Luciano, Laure; et al.
Abstract : Chronic constipation is a common symptom that regularly affects the quality of life of adult patients. Its treatment is mainly based on dietary rules, laxative drugs, perineal rehabilitation and surgical treatment. The French National Society of Coloproctology offers clinical practice recommendations on the basis of the data in the current literature, including those on recently developed treatments. Most are noninvasive, and the main concepts include the following: stimulant laxatives are now considered safe drugs and can be more easily prescribed as a second-line treatment; biofeedback therapy remains the gold standard for the treatment of anorectal dyssynergia that is resistant to medical treatment; transanal irrigation is the second-line treatment of choice in patients with neurological diseases, but it may also be proposed for patients without neurological diseases; and although interferential therapy may be a new promising treatment, it needs further evaluation. Abstract : Supplemental Digital Content is available in the text.